Urine neopterin: a new parameter for serial monitoring of disease activity in patients with systemic lupus erythematosus. Issue 11 (November 1994) - Lim, K L; Muir, K; Powell, R J
Abstract : OBJECTIVE--To investigate the role of serial measurement of urine neopterin concentration in monitoring the progression of systemic lupus erythematosus (SLE) disease activity scored using the British Isles Lupus Assessment Group (BILAG) index. METHODS--We followed prospectively 68 unselected SLE patients for a total of 464 patient months during which 233 separate assessments were carried out. At each assessment, urine neopterin, determined by high performance liquid chromatography, together with erythrocyte sedimentation rate (ESR) and plasma C3, C4, and C3d were measured and the SLE disease activity scored by a single observer. Serial data sets were analysed using time series modelling techniques. RESULTS--Single time point analysis showed a significant increase in urine neopterin concentrations in 14 patients who suffered flares of their disease during the study period (p = 0.02). Thirty patients with active disease went into disease remission with significant decreases in their urine neopterin values (p = 0.02). In the time series analysis, a statistically significant association was found between serial concentrations of urine neopterin and BILAG score (r = 0.6, p < 0.05); no other study parameter (ESR and serum C3, C4, and C3d) mirrored SLE disease activity as effectively. CONCLUSIONS--This study provides initial evidence that changes in urine concentrations of neopterin are significantly correlated with fluctuations in disease activity over time, scored using the BILAG index, amongst individual patients with SLE. Consequently, serial urine neopterin measurements appear to be clinically useful for monitoring disease activity and may contribute substantially to therapeutic decision making in these patients.